Photoreceptor protection: significance of docosanoids and elovanoids 1: docosahexaenoic acid (DHA) - Bazan, Nicolas (Henry Stewart Talks, 2019)
Biosynthesis of docosanoids, Essential fatty acids, Neuroprotective bioactivity during oxidative stress, AdipoR1 as a regulatory switch of the DHA